Comparison of nicotine concentration and pH of commercially available smokeless tobacco products - Vijaya Hegde; Ambili Nanukuttan (Wolters Kluwer Medknow Publications, 2017)
Aim: This study aims to compare the nicotine concentration and pH in commercially available smokeless tobacco (ST) products. Materials and Methods: The pH level and nicotine concentration were determined in five ST products which were obtained from local markets. The pure form of nicotine was used as a standard which was obtained from Sigma-Aldrich Chemicals, Bengaluru. An extract of each product was prepared and the nicotine concentration was determined in triplicates by spectrophotometric method. The estimation of pH was done using digital pH meter. Results: The analysis showed that nicotine concentration was highest in plain tobacco followed by ghutka, khaini, pan masala, and supari, respectively. The pH was highest in khaini followed by pan masala, supari, ghutka, and plain tobacco, respectively. Conclusion: The study results showed that there is a difference in nicotine concentration and pH among ST products. Although other factors could influence the rate of nicotine absorption from ST, manipulating tobacco pH appears to be the primary means by which the speed of nicotine absorption is determined in ST products.